Uniform Magnesium Electrodeposition via Synergistic Coupling of Current Homogenization, Geometric Confinement, and Chemisorption Effect. Issue 26 (31st May 2021) - Song, Zihao; Zhang, Zhonghua; Du, Aobing; Dong, Shanmu; Li, Guicun; Cui, Guanglei
Abstract: Unevenly distributed magnesium (Mg) electrodeposits have emerged as a major obstacle for Mg‐metal batteries. A comprehensive design matrix is reported for 3D magnesiophilic hosts, which regulate the uniform Mg electrodeposition through a synergistic coupling of homogenizing current distribution, geometric confinement, and chemisorptive interaction. Vertically aligned nitrogen‐ and oxygen‐doped carbon nanofiber arrays on carbon cloth (denoted as "VNCA@C") are developed as a proof of concept. The evenly arranged short nanoarray architecture helps to homogenize the surface current density and the microchannels built in this 3D host allow the preferential nucleation of Mg due to their geometrical confinement effect. Besides, the nitrogen‐/oxygen‐doped carbon species exhibit strong chemisorptive interaction toward Mg atoms, providing preferential nucleation sites as demonstrated by first‐principle calculation results. Electrochemical analysis reveals a peculiar yet highly reversible microchannel‐filling growth behavior of Mg metals, which empowers the delicately designed VNCA@C host with the ability to deliver a reduced nucleation overpotential of 429 mV at 10.0 mA cm −2 and an elongated Mg plating/stripping cycle life (110 cycles) under high current density of 10.0 mA cm −2 . The proposed design matrix can be extended to other metal anodes (such as lithium and zinc) for high‐energy‐density batteries. Abstract : Through a synergistic coupling of homogenizing current distribution, geometric confinement, and chemisorptive interaction, a 3D vertically aligned nitrogen‐ and oxygen‐doped carbon nanofiber array structure on carbon cloth can regulate the uniform Mg electrodeposition and realize a reversible magnesium‐metal anode with high areal capacity, much better kinetics, and improved cycle life.